Comparative genomics of vertebrate Fox cluster loci - Wotton, K; Shimeld, S (BioMed Central, 2006)
Background: Vertebrate genomes contain numerous duplicate genes, many of which are organised into paralagous regions indicating duplication of linked groups of genes. Comparison of genomic organisation in different lineages can often allow the evolutionary history of such regions to be traced. A classic example of this is the Hox genes, where the presence of a single continuous Hox cluster in amphioxus and four vertebrate clusters has allowed the genomic evolution of this region to be established. Fox transcription factors of the C, F, L1 and Q1 classes are also organised in clusters in both amphioxus and humans. However in contrast to the Hox genes, only two clusters of paralogous Fox genes have so far been identified in the Human genome and the organisation in other vertebrates is unknown. Results: To uncover the evolutionary history of the Fox clusters, we report on the comparative genomics of these loci. We demonstrate two further paralogous regions in the Human genome, and identify orthologous regions in mammalian, chicken, frog and teleost genomes, timing the duplications to before the separation of the actinopterygian and sarcopterygian lineages. An additional Fox class, FoxS, was also found to reside in this duplicated genomic region. Conclusion: Comparison of loci identifies the pattern of gene duplication, loss and cluster break up through multiple lineages, and suggests FoxS1 is a likely remnant of Fox cluster duplication.